Baseline Characteristics and Treatment Response of Patients from the Philippines in the CHIMES Study. (October 2014) - Navarro, Jose C.; Gan, Herminigildo H.; Lao, Annabelle Y.; Baroque, Alejandro C.; Hiyadan, John H. B.; Chua, Carlos L.; Jose, Ma. Cristina San; Advincula, Joel M.; Lee, Chun Fan; Bousser, Marie-Germaine; Chen, Christopher L. H.
Background: The CHIMES Study compared MLC601 with placebo in patients with ischemic stroke of intermediate severity in the preceding 72 h. Sites from the Philippines randomized 504 of 1099 (46%) patients in the study. We aimed to define the patient characteristics and treatment responses in this subgroup to better plan future trials. Methods: The CHIMES dataset was used to compare the baseline characteristics, time from stroke onset to study treatment initiation, and treatment responses to MLC601 between patients recruited from Philippines and the rest of the cohort. Treatment effect was analyzed using end-points at month 3 as described in the primary publication, that is, modified Rankin Score, National Institutes of Health Stroke Scale, and Barthel Index. Results: The Philippine cohort was younger, had more women, worse baseline National Institutes of Health Stroke Scale, and longer time delay from stroke onset to study treatment compared with the rest of the cohort. Age ( P = 0·003), baseline National Institutes of Health Stroke Scale ( P < 0·001), and stroke onset to study treatment initiation ( P = 0·016) were predictors of modified Rankin Score at three-months. Primary analysis of modified Rankin Score shift was in favor of MLC601 (adjusted odds ratio 1·41, 95% confidence interval 1·01–1·96). Secondary analyses were likewise in favor of MLC601 for modified Rankin Score dichotomy 0–1, improvement in National Institutes of Health Stroke Scale (total and motor scores), and Barthel Index. Conclusions: The treatment effects in the Philippine cohort were in favor of MLC601. This may be due to inclusion of more patients with predictors of poorer outcome.